Screening for Partner Postpartum Depression: A Systematic Review. Issue 3 (May 2023) - Le, Joria; Alhusen, Jeanne; Dreisbach, Caitlin
Abstract: Background: Postpartum depression is a significant mental health condition affecting an estimated 7% to 20% of women, with higher rates among individuals with increased risk factors. Most research on postpartum depression has focused on mothers, with less recognition of the mental health changes experienced by their partners. Research suggests almost 20% of partners may experience postpartum depression, yet our understanding is limited. An enhanced understanding of postpartum depression in a birthing person's partner is critical, given the mental and physical health sequelae associated with depression. Purpose: The purpose of this review was to systematically examine the current tools available to assess partner postpartum depression. Methods: We conducted a systematic review according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Eligible studies were identified using selected key terms in PubMed, Cumulative Index to Nursing and Allied Health Literature (CINAHL), Web of Science, and Ovid MEDLINE. Studies were included if they assessed partner depressive symptoms and identified the specified use of a tool or screening measure. Results: Seventeen studies met inclusion criteria. Seven different measures were used to assess postpartum depression. The Edinburgh Postnatal Depression Scale (EPDS) was used in 16 out of the 17 studies for depression assessment. Clinical Implications: Routine screening of partners for postpartum depression should be recommended as part of standard care. Nurses are critical liaisons for assessing risk and connecting relevant and timely resources to birthing people and their partners. Identifying the available screening tools may help to avoid adverse clinical outcomes associated with increased symptom severity and burden. Abstract : Most of the research on postpartum depression has focused on new mothers, however their partners can experience depression during postpartum as well. In this systematic review, articles that described screening tools for partner postpartum depression are evaluated. Recommendations for nursing practice are presented.